Share Jesus without fear - Fay, William; Linda Evans Shepherd (Nashville, TN Broadman & Holman Publishers, 1999)
In recent years, the Share Jesus without Fear book and its growing family of ancillary products have sparked a faith-sharing movement that continues to gain momentum. It began with the jaw-dropping story of William Fay, once a money-driven businessman wit
Keywords: Witness bearing (Christianity) Evangelistic work. Apologetics